Pengukuran Kualitas Aplikasi Custody Berdasarkan ISO 25010 Menggunakan Otomatisasi Pengujian Blackbox - Alief Fitriyanto Wijaya; Bheta Agus Wardijono (STMIK Budi Darma, 2023)
Custodian bank while running their business operational using an application that help them to handle various daily transaction like subscription, redemption, and switching. To ensure that the application is comply with the needs, testing phase is important processes where an application is feasible to use or not. Automation testing is a testing that conduct using tools to compare the expected result with the actual result. This research using black box testing method with the combination of equivalence partitioning and boundary value analysis technique and also using Katalon Studio as automation testing tool. The final result of this research then will be measure whether the Custody application has met the ISO 25010 standard or not. The final result of the research is based on testing using black box method with the combination of equivalence partitioning dan boundary value analysis technique using Katalon Studio are from the 28 test cases developed, all the test cases has passed the testing. The testing is conduct in Custody application at subscription and dividend menu. And then, after doing testing, the result of the testing is measured using ISO 25010 standard in 3 characteristics. They are functional suitability aspect, the result isall the testing has passed and get 100% percentage, compatibility aspect the result is there’s an issue with the website since it’s not using HTTPS, compatibility aspect using 3 aspects they are instrumentation, consistency, and simplicity. All the aspects has fulfilled the criteria of maintainability aspect